Benzyloxycalix[8]arene: a new valuable support for NHC palladium complexes in C–C Suzuki–Miyaura couplings. Issue 39 (14th September 2018) - Abdellah, Ibrahim; Kasongo, Pauline; Labattut, Axel; Guillot, Régis; Schulz, Emmanuelle; Martini, Cyril; Huc, Vincent
Abstract : Benzyloxycalix[8]arene supported catalysts bearing N-heterocyclic carbene palladium complexes on each subunit were readily synthesized. Abstract : Benzyloxycalix[8]arene supported catalysts bearing N-heterocyclic carbene palladium complexes on each subunit were readily synthesized. Intermediates and catalysts were fully characterized, allowing for a fine control of their structure. X-ray diffraction analysis confirmed the formation of a calix[8]arene bearing eight well-defined NHC palladium complexes. The macrocyclic structure of calix[8]arenes allowed for a scalable and chromatography-free catalyst synthesis under homogeneous conditions, while the catalytic reaction proceeded under heterogeneous conditions, just by changing the nature of the solvent. Indeed, when used as a suspension in ethanol, a high TON and TOF were obtained through a large panel of functionalized brominated substrates in C–C Suzuki–Miyaura couplings, with low metal contamination after simple filtration.